Multihop wireless networks : opportunistic routing - Zeng, Kai.; Lou, Wenjing; Li, Ming, 1985- (Hoboken, N.J. : Wiley, 2011)
'This book provides an introduction to opportunistic routing an emerging technology designed to improve the packet forwarding reliability, network capacity and energy efficiency of multihop wireless networksThis book presents a comprehensive background to the technological challenges lying behind opportunistic routing. The authors cover many fundamental research issues for this new concept, including the basic principles, performance limit and performance improvement of opportunistic routing compared to traditional routing, energy efficiency and distributed opportunistic routing protocol design, geographic opportunistic routing, opportunistic broadcasting, and security issues associated with opportunistic routing, etc. Furthermore, the authors discuss technologies such as multi-rate, multi-channel, multi-radio wireless communications, energy detection, channel measurement, etc. The book brings together all the new results on this topic in a systematic, coherent and unified presentation and provides a much needed comprehensive introduction to this topic.Key Features: Addresses opportunistic routing, an emerging technology designed to improve the packet forwarding reliability, network capacity and energy efficiency of multihop wireless networks Discusses the technological challenges lying behind this new technology, and covers a wide range of practical implementation issues Explores many fundamental research issues for this new concept, including the basic principles of opportunistic routing, performance limits and performance improvement, and compares them to traditional routing (e.g. energy efficiency and distributed opportunistic routing protocol design, broadcasting, and security issues) Covers technologies such as multi-rate, multi-channel, multi-radio wireless communications, energy detection, channel measurement, etc. This book provides an invaluable reference for researchers working in the field of wireless networks and wireless communications, and Wireless professionals. Graduate students will also find this book of interest'--
'This book presents a comprehensive background to the technological challenges lying behind opportunistic routing'--
Includes bibliographical references and index.
Keywords: Ad hoc networks (Computer networks); Radio relay systems; TECHNOLOGY & ENGINEERING / Telecommunications